Pembentukan Data Mart Menggunakan Metode Generalization - Sugita Aryandana, I Gede; Sukarsa, I Made; Buana, Putu Wira (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 3 Desember 2016, 2016)
Technology today causing the data needs of an agency or company to process the data or analyze data quickly, dense and higher. Companies or institutions want the data analysis process can save time as much as possible. The data warehouse is a data analysis technology that is useful to resolve the issue. The data warehouse is a repository of data that is useful to accommodate all the history data held by agencies or companies. Data marts are small part of the data warehouse. Data mart is focused on a single subject. This study uses a generalization method to perform the process of establishing a data mart. Generalization is a useful method to reduce or narrow the differences in the data based Subclass. Subclass were integrated into a Superclass useful to collect some data from the Subclass. Subclass is the data that is more descriptive. Superclass is more general in nature of data. The result obtained is a collection of some Subclass predetermined or selected later formed a Superclass useful to accommodate the resources of the Subclass.
Keywords: Data Warehouse; Data Mart Generalization.